Analisa Kualitatif Asam Retinoat pada Sediaan Krim Malam di Pasar Klaten dengan Metode Kromatografi Lapis - Anita Agustina S; Choiril HM; Maylita ED (Universitas Muhammadiyah Klaten, 2019)
Some cosmetics are still found chemicals that are harmful to the skin, such as Mercury, Hydroquinone, Retinoic Acid. These materials have been banned. so researchers are interested in researching Retinoic Acid. Retinoic acid is a hard drug and can only be purchased by prescription from a doctor, but in reality many cosmetics containing retinoic acid are sold freely. Side effects caused include: making the skin feel burned, carcinogenic and teratogenic. The purpose of this study was to carry out a qualitative analysis of retinoic acid compounds in night creams using the thin layer chromatography (TLC) method. The research method was an observational study with the silica gel 60 F 254 nm stationary phase and the n-hexane: ethanol mobile phase (6: 4). From the research that has been done shows the average Rf price of creamA is 0.94; cream B that is 0.90; C cream that is 0.92; creamD is 0.94; cream that is 0.89; while the standard Rf is 0.97. when observed under UV light 254 nm has a dark green spot that corresponds to a standard retinoic acid has a dark green spot so that it can be stated that A, B cream, C cream, D cream, and E cream contain positive retinoic acid.